1999
DOI: 10.1111/1467-9280.00152
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Time (LET) or Scalar Expectancy Theory (SET)? A Critical Test of Two Models of Timing

Abstract: Abstract-Two theories of timing, scalar expectancy theory (SET) and learning to time (LeT) During the past 15 years or so, the study of how animals time events has been guided to a large extent by two competing theories, the scalar expectancy theory (SET; Gibbon, 1977Gibbon, , 1991 and the behavioral theory of timing (BeT; Killeen & Fetterman, 1988). The present study reports the results of an experiment for which these two theories make substantially different predictions. However, instead of focusing on Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
77
1
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 16 publications
15
77
1
7
Order By: Relevance
“…First, it is possible that the pigeons used their own behavior to mediate comparison choice. Machado and Keen (1999) trained pigeons on two temporal discriminations, one involving the discrimination between samples of 1 and 4 sec, the other, the discrimination between samples of 4 and 16 sec. They found that most of their pigeons began pecking the sample after it had been presented for more than 1 sec, but they stopped pecking after about 6 sec.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible that the pigeons used their own behavior to mediate comparison choice. Machado and Keen (1999) trained pigeons on two temporal discriminations, one involving the discrimination between samples of 1 and 4 sec, the other, the discrimination between samples of 4 and 16 sec. They found that most of their pigeons began pecking the sample after it had been presented for more than 1 sec, but they stopped pecking after about 6 sec.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these possibilities, the exact nature of the underlying mechanisms and interactions between the SET components and the timing deficit in high UE scorers is clearly in need of further exploration. Alternatively, the Learning to Time theory (LeT) 11,52 argues that timing occurs in terms of a chain of behavioral states initiated by environmental stimuli, with each state holding associative links with available responses 11 . In terms of the present task, these associative links are argued to differ in strength between each behavioral state and the responses available (i.e., S and L), with earlier behavioral states in the chain more strongly linked to the "short" choice, whilst later behavioral states are more strongly linked to the L choice.…”
Section: Timing and Schizotypy -14mentioning
confidence: 99%
“…The probe tests that we used were similar, but not identical, to probe tests given by Machado and Keen (1999 Both panels show that accuracy was higher under prospective cuing conditions (dark hatched bars) than under retrospective conditions (light stippled bars). This difference in cuing condition was consistent across all birds and test ranges except for Pigeon 52 in the long set.…”
Section: Resultsmentioning
confidence: 88%
“…The probe tests were similar, but not identical, to probe tests used by Machado and Keen (1999). In their procedure, the choice-key colors cuing the test range were a houselight and a white center-key light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation